Transport of thyroid hormones via the choroid plexus into the brain: the roles of transthyretin and thyroid hormone transmembrane transporters - Richardson, Samantha J.; Wijayagunaratne, Roshen C.; D'Souza, Damian G.; Darras, Veerle M.; Van Herck, Stijn L. J. (Frontiers in Neuroscience, 2015)
Thyroid hormones (THs) are key players in regulating brain development. In humans, insufficient THs during gestation can lead to cretinism and mental retardation. Thus, transfer of appropriate quantities of THs from the blood into the brain at specific stages of development is critical. The choroid plexus forms the blood-cerebrospinal fluid (CSF) barrier. In reptiles, birds and mammals, the main protein synthesised by the choroid plexus is a TH distributor protein: transthyretin (TTR). TTR is secreted into the CSF and moves THs from blood into CSF. The structure of TTR has been highly conserved, implying strong selection pressure and an important function. The choroid plexus develops faster than other parts of the brain. In precocial animals rapid brain growth occurs prior to birth, whereas in altricial animals it is after birth. For both groups, maximal TTR expression in the choroid plexus is just prior to rapid brain growth, suggesting that choroid plexus-derived TTR moves THs from blood into CSF just prior to when THs are required for rapid brain growth. TTR null mice have no overt phenotype, bringing into question the role of TTR synthesised by the choroid plexus. This has been in part resolved by the discovery of TH transmembrane transporters, which have been identified in many tissues (including choroid plexus) and transport THs into and out of cells. In mammals, TTR binds T4 (pro-TH) with higher affinity than T3 (active TH). In all other vertebrates, TTR binds T3 with higher affinity than T4. As mammals are the exception, we should not base our thinking solely on mammalian data. THs enter the choroid plexus via TH transmembrane transporters and leave the choroid plexus to enter the CSF via either TH transmembrane transporters or via choroid plexus-derived TTR secreted into the CSF. The quantitative contribution of each route during development remains to be elucidated. This is part of a review series on ontogeny and phylogeny of brain barrier mechanisms.